Oil Industry in Kuban in 1928—1935: Problems and Factors of Production Growth - D. A. Salfetnikov (Научный диалог)
The question of the development of the oil industry in the Kuban regions in the late 1920s and in the first half of the 1930s is considered. Attention is paid to the state of oil production and oil refining at the end of the NEP, the reasons for the difficult situation in the oil industry. The results of a comparative analysis of the potential and activities of the corresponding Kuban refineries that were part of various oil trusts are presented. The classification of enterprises is proposed depending on their profile (oil production and oil refining) and production value. A review of the production life of these enterprises is carried out. Their role in the regional economy and in strengthening interregional economic ties is assessed. The relevance of the study is due to the need to consider the degree of participation of oil industry enterprises in the Kuban in solving important economic problems that go beyond this region. The situation in oil production and oil refining as an important segment of heavy industry located on the territory of an agricultural region is analyzed and reconstructed in the article. Questions are raised about the specifics of the development of the oil industry in the Kuban, about the form of subordination of its enterprises. Particular attention is paid to the problems of staffing, technical equipment of oil producing and oil refineries and their impact on the implementation of complex planned targets. It has been proved that the dynamics of the development of the Kuban oil-bearing regions and the development of oil refineries depended on the introduction of new drilling methods, on the intensification of exploitation of both developed and new oil-bearing regions.